Relação amorosa e tentativa de suicídio na adolescência : uma questão de (des)amor - Azevedo, Ana Karina Silva (2006)
Suicide rates have been rising all over the world. In Rio Grande do Norte state, a study carried out by Dutra (1999) investigated suicide rates among youngsters and found that in 1997 alone 244 cases of suicide attempt were registered. The author took an interest in studying this phenomenon among adolescents after reviewing Dutra s study and the technical literature on suicide. In addition to that, another topic caught her attention and raised new research questions: suicide attempts motivated by love, i.e., the end of a relationship, the fantasy of being abandoned by a partner. These have made the author to question how love manifested itself among adolescents and how it could become a reason for adolescents to give up their lives. Based on the data she analyzed and the research questions she developed, her research objective was to understand how adolescents who have attempted suicide because of love-related reasons have gone through this experience. The theoretical reference for the research was the Client-centered Therapy and more specifically, the construct self , according to Carl Rogers. The methodological strategy was inspired by the existential-phenomenological strategy. It used the narrative as a research instrument, inspired by the work of Walter Benjamim (1994) which was developed into a research strategy by Schmidt (1990). Four youngsters (three male and one female) have participated in this study. They have attempted suicide for love-related reasons during dolescence, when they were 12 to 18 years old. The interviews were recorded on cassette tapes, transcribed and literalized into narratives. The understanding of the narratives was based on the meanings that emerged from the youngsters speeches, as well as from the moments that touched the author. These moments highlighted the meaning of the experience of giving up life and the experience of love-based relationship as experienced by the youngsters. The study detected, among the adolescents who were interviewed, the existence of impulsiveness related to the suicide attempt. Also, the majority of the interviewees came from unstructured family backgrounds and had lost of one of their parents or had to face their parents divorce. The suicide was attempted by these youngsters through the ingestion of medicines. The research also revealed that the youngsters had regretted attempting suicide and felt guilty about it. With regards to their self-evaluation, the author observed that the youngsters had low self-esteem, negative perceptions about themselves and distorted views of themselves. These findings helped the author to reflect on the close relationship between the construct self and the suicide attempt. She also observed that a few factors, i.e., family context, education, social and cultural values, have influenced the way the youngsters perceived themselves . The results of this research confirm the idea that we have to understand the suicide attempt as a multi-determined phenomenon. This study contributed to the analysis and reflection on the factors that contribute to suicide attempts thus providing a foundation for the development of public health programs and policies to deal with this topic